Teaching critical thinking and cultural intelligence via virtual exchange: a practice report on the utilization of research-based principles to support and assess learning outcomes - Lander Sims (University of Groningen Press, 2022)
While it is appealing to consider the potential benefits of incorporating virtual exchange and other technology-based tools when designing a learning experience, it is irresponsible to assume that technology in-and-of itself has the power to improve learning outcomes. Research-supported pedagogy and theory must form the basis of any attempt to incorporate virtual exchange into a learning activity. This paper presents a detailed examination of an undergraduate liberal arts course built on research-supported theories and practices to support learning outcomes, including collaborative cognitive load theory, the cognitive theory of multimedia learning, and instruction based on self-explanation and self-reflection. Initial assessment of the course suggests success in achieving learning outcomes related to critical thinking and intercultural discourse but highlights the need for objective data to support these claims. As virtual exchange gains momentum, it is necessary to continually assess and improve its utilization to guarantee its educational value.